La imagen del laberinto en las novelas regionatas de Juan Benet - Carrera, Miguel (Amaltea. Revista de Mitocrítica, 2009)
It is a common place to describe Benet’s works as “labyrinthine”. This is based on their remarkable complexity, but also on other structural and thematic factors. Besides, the correspondences with Theseus and the Minotaur’s myth give rise to a fruitful and revealing analogy. It is our intention, thus, to unify the novels of the Región saga under such concept, from the reading level to their content, making equal, as far as possible, the author’s, the reader’s and the characters’ perspectives. Throughout all these levels, the labyrinth motif refers to two of the main traits of the Benetian literature: irrationality and demythification.